State institutions and their role in supporting the integration of internally displaced persons: a management perspective on migration processes - Kapinus, Oleksandra; Petrukha, Nina; Plaksun, Anton; Velykyi, Yevhenii; Havrik, Roman (Universidad Hemisferios, 2025)
In the context of migration growth, the challenges of regulating migration are exacerbated, increasing the burden on state structures responsible for migrant adaptation and migration control. To determine the effectiveness of state structures in managing migration processes, the following objectives were formulated: to study international recommendations on migrant rights; to identify countries with the highest levels of migration; to study the activities of state immigration authorities in the country with the largest number of migrants; to create a unified coefficient for determining positive migration; and to assess the state of protection of the rights of internally displaced persons (IDPs) in Ukraine. The study used bibliographic, analytical, deductive, inductive, synthetic, logical comparison, graphical, correlation analysis, and mathematical modeling methods. The results revealed that the United States (U. S.) leads the number of immigrants, and that the use of the Human Development Index (HDI) to analyze migration is ineffective. Thus, a mathematical calculation of the positive migration coefficient is proposed based on the criteria of the international agreements of the Global Commission on International Migration. This paper presents the structure of the state administration of IDPs in Ukraine in comparison with international requirements for respecting the rights of migrants, and identifies its weaknesses and strengths.